PERCOBAAN PENYERAPAN LIMBAH INDUSTRI MENGGUNAKAN KARBON AKTIF DARI BATUBARA TANJUNG TABALONG, KALIMANTAN SELATAN - A. Gani, M. Ulum (Jurnal Teknologi Lingkungan Universitas Trisakti, 2008)
Research of Industrial Wastewater Absorption using Coal Activated Carbon from Tanjung Tabalong South Kalimantan. The research of absorbing capability of carbon active from Tanjung Tabalong coal was carried out to organic and unorganic elements in industrial waste to identify the absorption capability of carbon active coal for refining of industrial waste. The research comprised of carbonization and activation process as well as the experimentation of the active-carbon absorption capability. The carbonization process was carried out at low temperature of 600oC which produced semi-coke, while activation process was carried out to semi coke at temperature of 700oC with activation time of 120 minutes which produced active carbon. The experimentation of absorption capability was performed to COD (Chemical Oxygen Demand). Parameters studied are 2.5 and 9.0 grms active carbon for 250 ml and 300 ml to COD waste with agitation time of 30; 60 and 90 minutes respectively. The result of experimentation both absorption of COD were analyzed with AAS (Atomic Absorption Spectrophotometer) shown that the utilization of 2.5 grm active carbon can absorp COD waste ranging of 6.9-67.5 grm. While for the utilization of 9 grms can absorp COD waste ranging of 88.9-100 %. The higher of active carbon and the longer time of agitation used in this experiment, the higher the absorption of COD and TSS. Â Â Abstract in Bahasa Indonesia:Â Penelitian kemampuan penyerapan karbon aktif dari batubara Tanjung Tabalong, Kalimantan Selatan telah dilakukan terhadap unsur-unsur organik dan un organic dalam limbah industeri untuk identifikasi kemampuan penyerapan carbon aktif untuk memurnikan limbah industri. Peneltian terdiri dari proses karbonisasi dan aktivasi serta percobaan kemampuan penyerapam karbon aktif. Proses karbonisasi dilakukan pada suhu 600oC yang menghasilkan semikokas, sedangkan proses aktivasi dilakukan terhadap semikokas pada suhu 700oC dengan waktu aktivasi 120 menit yang menghasilkan karbon aktif. Percobaan kemampuan penyerapan karbon aktif dilakukan terhadap limbah COD (chemical oxygen demand). Parameter yang digunakan adalah 2,5 dan 9 grm karbon aktif masing-masing untuk 250 ml dan 300 ml limbah COD dengan masing-masing waktu pengadukan 30,60 dan 90 menit. Hasil percobaan yang dianalisa dengan AAS (Atomic Absorption Spectrophotometer) menunjukkan bahwa penggunaan 2,5 grm karbon aktif dapat menyerap limbah COD masing-masing sebesar 6.9-67,5 % sedangkan untuk pemakaian 9 grm masing-masing dapat menyerap COD sebesar 88,9-100 % Makin tinggi karbon aktif dan makin lama waktu pengadukan yang digunakan dalam percobaan ini, maka semakin tinggi pula kemampuan penyerapan limbah COD.